Regioselective 1,4-trifluoromethylation of α,β-unsaturated ketones via a S-(trifluoromethyl)diphenylsulfonium salts/copper system - Okusu, Satoshi; Sugita, Yutaka; Tokunaga, Etsuko; Shibata, Norio (Beilstein Journal of Organic Chemistry, 2013)
Regioselective conjugate 1,4-trifluoromethylation of α,β-unsaturated ketones by the use of shelf-stable electrophilic trifluoromethylating reagents, S-(trifluoromethyl)diphenylsulfonium salts and copper under mild conditions is described. A wide range of acyclic aryl–aryl–enones and aryl–alkyl–enones were converted into β-trifluoromethylated ketones in low to moderate yields.
Keywords: 1,4-addition; copper; fluorine; Michael addition; organo-fluorine; trifluoromethylation

(untitled) - Ma, J.-A.; Cahard, D. (Chem. Rev., 2008)

(untitled) - Shibata, N.; Mizuta, S.; Kawai, H. (Tetrahedron: Asymmetry, 2008)

(untitled) - Prakash, G. K. S.; Yudin, A. K. (Chem. Rev., 1997)

(untitled) - Prakash, G. K. S.; Mandal, M. (J. Fluorine Chem., 2001)

(untitled) - Billard, T.; Langlois, B. R. (Eur. J. Org. Chem., 2007)

(untitled) - Kawai, H.; Yuan, Z.; Tokunaga, E.; Shibata, N. (Org. Biomol. Chem., 2013)

(untitled) - Prakash, G. K. S.; Jog, P. V.; Batamack, P. T. D.; Olah, G. A. (Science, 2012)

(untitled) - Billard, T.; Bruns, S.; Langlois, B. R. (Org. Lett., 2000)

(untitled) - Singh, R. P.; Kirchmeier, R. L.; Shreeve, J. M. (Org. Lett., 1999)

(untitled) - Matsukawa, S.; Saijo, M. (Tetrahedron Lett., 2008)

(untitled) - Kawano, Y.; Kaneko, N.; Mukaiyama, T. (Bull. Chem. Soc. Jpn., 2006)

(untitled) - Large, S.; Roques, N.; Langlois, B. R. (J. Org. Chem., 2000)

(untitled) - Sosnovskikh, V. Y.; Sevenard, D. V.; Usachev, B. I.; Röschenthaler, G.-V. (Tetrahedron Lett., 2003)

(untitled) - Sosnovskikh, V. Y.; Usachev, B. I.; Sevenard, D. V.; Röschenthaler, G.-V. (J. Org. Chem., 2003)

(untitled) - Kawai, H.; Tachi, K.; Tokunaga, E.; Shiro, M.; Shibata, N. (Angew. Chem., Int. Ed., 2011)

(untitled) - Zemtsov, A. A.; Levin, V. V.; Dilman, A. D.; Struchkova, M. I.; Belyakov, P. A.; Tartakovsky, V. A.; Hu, J. (Eur. J. Org. Chem., 2010)

(untitled) - Furukawa, T.; Nishimine, T.; Tokunaga, E.; Hasegawa, K.; Shiro, M.; Shibata, N. (Org. Lett., 2011)

(untitled) - Sevenard, D. V.; Sosnovskikh, V. Y.; Kolomeitsev, A. A.; Königsmann, M. H.; Röschenthaler, G.-V. (Tetrahedron Lett., 2003)

(untitled) - Zemtsov, A. A.; Levin, V. V.; Dilman, A. D.; Struchkova, M. I.; Belyakov, P. A.; Tartakovsky, V. A. (Tetrahedron Lett., 2009)

(untitled) - Dilman, A. D.; Levin, V. V.; Belyakov, P. A.; Struchkova, M. I.; Tartakovsky, V. A. (Tetrahedron Lett., 2008)

(untitled) - Kawai, H.; Tachi, K.; Tokunaga, E.; Shiro, M.; Shibata, N. (Org. Lett., 2010)

(untitled) - Wilger, D. J.; Gesmundo, N. J.; Nicewicz, D. A. (Chem. Sci., 2013)

(untitled) - Shibata, N.; Matsnev, A.; Cahard, D. (Beilstein J. Org. Chem., 2010)

(untitled) - Matsnev, A.; Noritake, S.; Nomura, Y.; Tokunaga, E.; Nakamura, S.; Shibata, N. (Angew. Chem., Int. Ed., 2010)

(untitled) - Noritake, S.; Shibata, N.; Nakamura, S.; Toru, T.; Shiro, M. (Eur. J. Org. Chem., 2008)

(untitled) - Eisenberger, P.; Gischig, S.; Togni, A. (Chem.–Eur. J., 2006)

(untitled) - Bizet, V.; Pannecoucke, X.; Renaud, J.-L.; Cahard, D. (J. Fluorine Chem., 2013)

(untitled) - Maruoka, K.; Shimada, I.; Imoto, H.; Yamamoto, H. (Synlett, 1994)